2011
DOI: 10.1186/alzrt85
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term cognitive outcome in Alzheimer's disease

Abstract: IntroductionThe objective of this study was to describe the longitudinal cognitive outcome in Alzheimer's disease (AD) and analyze factors that affect the outcome, including the impact of different cholinesterase inhibitors (ChEI).MethodsIn an open, three-year, nonrandomized, prospective, multicenter study, 843 patients were treated with donepezil, rivastigmine, or galantamine in a routine clinical setting. At baseline and every six months, patients were assessed using several rating scales, including the Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(132 citation statements)
references
References 54 publications
6
117
2
Order By: Relevance
“…Therefore, it is assumed that those individuals require a relatively larger burden of AD pathology at the onset of clinical symptoms [30]. The brain-reserve hypothesis is supported by the observation of faster cognitive decline among patients with more years of education in several [19,29,31] but not all [32,33] studies. Nevertheless, most previous studies have demonstrated that the participants' level of education does not influence survival time after the onset or diagnosis of AD [6,10,13,31].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Therefore, it is assumed that those individuals require a relatively larger burden of AD pathology at the onset of clinical symptoms [30]. The brain-reserve hypothesis is supported by the observation of faster cognitive decline among patients with more years of education in several [19,29,31] but not all [32,33] studies. Nevertheless, most previous studies have demonstrated that the participants' level of education does not influence survival time after the onset or diagnosis of AD [6,10,13,31].…”
Section: Discussionmentioning
confidence: 83%
“…Participation in studies and variations in mortality may be more influenced by other factors among the oldest patients, such as manifestation of the disease, concomitant medical disorders, and psychiatric symptoms. Nevertheless, a recent study from our group showed a better cognitive response to ChEI therapy and a slower disease progression among older individuals with AD [19]. The oldest individuals might have a reduced cognitive reserve because of their advanced age that can lead to an earlier manifestation of the typical AD symptoms, worse performance on standardized cognitive tests, and hence earlier detection of the disease.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Whether the gender differences are due to the fact that women live longer than men, is still a subject of debate, however several meta-studies have shown that women indeed have an increased risk of developing AD (19)(20)(21). Moreover, there are two studies showing that men with AD respond better to cholinesterase inhibitors treatment than women (22,23). Dementia with Lewy bodies, on the other hand, is a male-dominant disease (2), which further indicates that the mechanisms underlying these two neurodegenerative diseases differ.…”
Section: Introductionmentioning
confidence: 99%